Low-frequency electrical stimulation enhances the effectiveness of phenobarbital on GABAergic currents in hippocampal slices of kindled rats. (25th August 2016) - Asgari, Azam; Semnanian, Saeed; Atapour, Nafiseh; Shojaei, Amir; Moradi-Chameh, Homeira; Ghafouri, Samireh; Sheibani, Vahid; Mirnajafi-Zadeh, Javad
Graphical abstract: Highlights: The interaction of low-frequency stimulation (LFS) and phenobarbital was studied. Application of LFS induced a long-term increase in GABAergic currents. Phenobarbital and LFS had positive interaction on GABAergic currents. Postsynaptic mechanisms may be involved in the above-mentioned interaction. Abstract: Low frequency stimulation (LFS) has been proposed as a new approach in the treatment of epilepsy. The anticonvulsant mechanism of LFS may be through its effect on GABAA receptors, which are the main target of phenobarbital anticonvulsant action. We supposed that co-application of LFS and phenobarbital may increase the efficacy of phenobarbital. Therefore, the interaction of LFS and phenobarbital on GABAergic inhibitory post-synaptic currents (IPSCs) in kindled and control rats was investigated. Animals were kindled by electrical stimulation of basolateral amygdala in a semi rapid manner (12 stimulations/day). The effect of phenobarbital, LFS and phenobarbital + LFS was investigated on GABAA -mediated evoked and miniature IPSCs in the hippocampal brain slices in control and fully kindled animals. Phenobarbital and LFS had positive interaction on GABAergic currents. In vitro co-application of an ineffective pattern of LFS (100 pulses at afterdischarge threshold intensity) and a sub-threshold dose of phenobarbital (100 μM) which had no significant effect on GABAergic currents alone, increased the amplitude and area under curve of GABAergic currents in CA1 pyramidal neurons of hippocampal slices significantly. Interestingly, the sub-threshold dose of phenobarbital potentiated the GABAergic currents when applied on the hippocampal slices of kindled animals which received LFS in vivo . Post-synaptic mechanisms may be involved in observed interactions. Obtained results implied a positive interaction between LFS and phenobarbital through GABAA currents. It may be suggested that a combined therapy of phenobarbital and LFS may be a useful manner for reinforcing the anticonvulsant action of phenobarbital.